Increased contact time and strength deficits in runners with exercise-related lower leg pain - Koldenhoven, R. M.; Virostek, A.; DeJong, A. F.; Higgins, M.; Hertel, J. (Journal of Athletic Training, 2020)
Context: Exercise-related lower leg pain (ERLLP) is common in runners. Objective: To compare biomechanical (kinematic, kinetic, and spatiotemporal) measures obtained from wearable sensors as well as lower extremity alignment, range of motion, and strength during running between runners with and those without ERLLP. Design: Case-control study. Setting: Field and laboratory. Patients or Other Participants: Of 32 young adults who had been running regularly (>10 mi [16 km] per week) for =3 months, 16 had ERLLP for =2 weeks and 16 were healthy control participants. Main Outcome Measure(s): Both field and laboratory measures were collected at the initial visit. The laboratory measures consisted of alignment (arch height index, foot posture index, navicular drop, tibial torsion, Q-angle, and hip anteversion), range of motion (great toe, ankle, knee, and hip), and strength. Participants then completed a 1.67-mi (2.69-km) run along a predetermined route to calibrate the RunScribe devices. The RunScribe wearable sensors collected kinematic (pronation excursion and maximum pronation velocity), kinetic (impact g and braking g), and spatiotemporal (stride length, step length, contact time, stride pace, and flight ratio) measures. Participants then wore the sensors during at least 3 training runs in the next week. Results: The ERLLP group had a slower stride pace than the healthy group, which was accounted for as a covariate in subsequent analyses. The ERLLP group had a longer contact time during the stance phase of running (mean difference [MD] = 18.00 ± 8.27 milliseconds) and decreased stride length (MD = -0.11 ± 0.05 m) than the control group. For the clinical measures, the ERLLP group demonstrated increased range of motion for great-toe flexion (MD = 13.9 ± 4.6°) and ankle eversion (MD = 6.3 ± 2.7°) and decreased strength for ankle inversion (MD = -0.49 ± 0.23 N/kg), ankle eversion (MD = -0.57 ± 0.27 N/kg), and hip flexion (MD = -0.99 ± 0.39 N/kg). Conclusions: The ERLLP group exhibited a longer contact time and decreased stride length during running as well as strength deficits at the ankle and hip. Gait retraining and lower extremity strengthening may be warranted as clinical interventions in runners with ERLLP.